Trophic transfer of TiO2 nanoparticles from marine microalga (Nitzschia closterium) to scallop (Chlamys farreri) and related toxicity. Issue 2 (21st December 2016) - Wang, Zhenyu; Xia, Bin; Chen, Bijuan; Sun, Xuemei; Zhu, Lin; Zhao, Jian; Du, Peng; Xing, Baoshan
Abstract : In the present study, the trophic transfer of TiO2 NPs from marine microalga Nitzschia closterium to scallop Chlamys farreri was investigated. over the potential risk and environmental impact of manufactured nanoparticles (NPs) have increased in marine environments. Abstract : Concerns over the potential risk and environmental impact of manufactured nanoparticles (NPs) have increased in marine environments. However, the potential transfer of NPs along the marine food chain and related toxicity are not well understood. In the present study, the trophic transfer of TiO2 NPs from marine microalga Nitzschia closterium to scallop Chlamys farreri was investigated. During trophic transfer, the related toxicity responses including lysosomal membrane stability, DNA damage and histopathological effects were also investigated. Moreover, the internalization of TiO2 NPs in the digestive gland of scallops was analyzed. The results showed that tissue burden of TiO2 NPs in the scallops through aqueous exposure was higher than dietary exposure. However, biomagnification of TiO2 NPs was observed in the gills, digestive gland, and mantle of scallops through microalga-scallop transfer. Increased lysosomal membrane permeability, DNA damage, and histopathological effects induced by TiO2 NPs were mainly observed in scallops after aqueous exposure rather than dietary exposure. Furthermore, TEM along with EDS analysis revealed the presence of TiO2 NPs in the nucleus of the digestive gland regardless of the exposure route. This study provides useful information on the trophic transfer of TiO2 NPs and their toxicity in marine microalga–bivalves food chain.